PENGEMBANGAN E-MODUL BERBASIS ANDROID PADA MATA PELAJARAN BAHASA INDONESIA KELAS V MI ASSALAM KOTA BATU - Aprilia, Chofifah Dwi (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Indonesian is a scientific discipline that directs students to have good and correct skills to practice using Indonesian, both written and spoken. The most important coverage of Indonesian in learning Indonesian at the Madrasah Ibtidaiyah (MI) level is writing and reading. One of the materials that requires reading and writing skills in class V is material about the main idea of a text. In this material, students are assigned to identify the main ideas and important information in non-fiction texts. However, in its implementation, teachers lack innovation in using learning media in the classroom, so students easily get bored and tend to be lazy about reading. Therefore, it is necessary to develop learning media that can increase student motivation. This research uses Research and Development (R&D) research with the Lee & Owens model. Development procedures using the Lee & Owens model include: (1) multimedia needs assessment and analysis; (2) multimedia instructional design; (3) multimedia development; (4) multimedia implementation; and (5) multimedia evaluation. The results of this research and development are in the form of an Android-based e-module learning media product for class V Indonesian language subject theme 5, subthemes 1,2,3 material "looking for main ideas and important information in a text". The media developed received media validation results of 88% with the criteria "very feasible" and obtained material validation results of 74% with the criteria "feasible". Apart from that, Android-based e-module media also received 89,86% of the assessment results from the attractiveness questionnaire filled out by students, so e-module media can be said to be an interesting learning medium. ABSTRAK Bahasa Indonesia adalah disiplin ilmu yang mengarahkan peserta didik agar mempunyai kecakapan yang bagus dan benar untuk mempraktikkan penggunaan bahasa Indonesia baik secara tulis maupun lisan. Cakupan bahasa Indonesia yang penting dalam pembelajaran bahasa Indonesia di tingkat Madrasah Ibtidaiyah (MI) adalah menulis dan membaca. Salah satu materi yang membutuhkan keterampilan membaca dan menulis di kelas V adalah materi tentang pokok pikiran pada sebuah teks. Dimana pada materi tersebut peserta didik ditugaskan untuk mengidentifikasi pokok pikiran dan informasi penting yang ada pada teks nonfiksi. Akan tetapi dalam pelaksanaanya guru kurang ber-inovasi dalam memanfaatkan media pembelajaran di kelas sehingga peserta didik mudah bosan dan cenderung malas untuk membaca. Oleh sebab itu perlu dikembangkan media pembelajaran yang dapat meningkatkan motivasi peserta didik. Penelitian ini menggunakan jenis penelitian Research and Development (R&D) dengan model Lee & Owens. Prosedur pengembangan dengan model Lee & Owens meliputi: (1) multimedia need assessment and analysis, (2) multimedia instructional design, (3) multimedia development, (4) multimedia implementation, dan (5) multimedia evaluation. Hasil penelitian dan pengembangan ini berupa produk media pembelajaran e-modul berbasis android pada mata pelajaran Bahasa Indonesia kelas V tema 5 subtema 1,2,3 materi “mencari pokok pikiran dan informasi penting dalam sebuah teks”. Media yang dikembangkan mendapatkan hasil validasi media sebesar 88% dengan kriteria “sangat layak” dan mendapatkan hasil validasi materi sebesar 74% dengan kriteria “layak”. Selain itu, media e-modul berbasis android juga mendapatkan hasil penilaian dari angket kemenarikan yang diisi oleh peserta didik sebesar 89,86% sehingga media e-modul dapat dikatakan sebagai media pembelajaran yang menarik.